Primary Healthcare Workers’ Awareness of Acute Rheumatic Fever & Rheumatic Heart Disease: A Study in Public Health Facilities in South Western Uganda - Ochora, Moses; Kyasimire, Lydia; Lutasingwa, Dan; Namata, Tamara; Ahmed, Muna; Favina, Alain; Kumbakumba, Elias; Nampijja, Dorah (Pediatric Health, Medicine and Therapeutics, 2024)
Introduction: Timely identification and treatment of a streptococcal throat infection prevents acute rheumatic fever (ARF) and its progression to Rheumatic Heart Disease (RHD). However, children in developing countries still present with established RHD, due to either missed, untreated or sub-optimally treated sore throats and ARF. We aimed to determine the level of knowledge, skills, and practices of primary health workers in South Western Uganda in providing care such children. Methods: We conducted a comparative quantitative cross-sectional study to assess knowledge, practices, and skills regarding the care of a child with a sore throat, ARF, and RHD. The responses were scored against a structured guide. The Fisher’s exact test and the chi- squared test with level of significance set at 0.05 were utilized to compare differences in knowledge, skills, and practices among health workers in private and public health facilities about ARF and RHD. Results: Eighty health workers from health facilities were interviewed in Mbarara district with a median age of 29.5 years (IQR 27.34) and median duration in practice of 5 years (IQR: 2, 10). On average, there were at least 3 children with sore throats weekly. At least 95% (CI: 87.25%–98.80%) of the health worker had awareness about ARF and RHD. Only 43.75% (95% CI: 33.18%–54.91%) had good knowledge about ARF and RHD. Majority, 61.25% (95% CI: 50.03%−71.39%) did not know the proper prophylaxis and investigations for a child with ARF. There were no statistically significant differences but a clinically meaningful differential in the level of knowledge among health workers in public and private facilities. Conclusion: The knowledge and skill level of health workers in primary healthcare facilities about ARF and RHD in South Western Uganda remains low, with no difference between practitioners in public and private facilities.
Keywords: Acute rheumatic fever; Rheumatic heart disease; Awareness; Knowledge; Healthcare provider